2020
DOI: 10.3390/metabo10050197
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics for Evaluating Flavor-Associated Metabolites in Plant-Based Products

Abstract: Plant-based diets (PBDs) are associated with environmental benefits, human health promotion and animal welfare. There is a worldwide shift towards PBDs, evident from the increased global demand for fresh plant-based products (PBPs). Such shifts in dietary preferences accompanied by evolving food palates, create opportunities to leverage technological advancements and strict quality controls in developing PBPs that can drive consumer acceptance. Flavor, color and texture are important sensory attributes of a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 127 publications
0
28
0
Order By: Relevance
“…The development of GC-O-MS has led to the identification of thousands of volatiles ( El Hadi et al, 2013 ; Pott et al, 2019 ), and numerous odor characteristics are distinguishable by the developed human sense of olfactory ( Pavagadhi and Swarup, 2020 ). Only a few dozen volatiles contribute substantially to flavor and only when their concentrations exceed the olfactory threshold ( Czerny et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of GC-O-MS has led to the identification of thousands of volatiles ( El Hadi et al, 2013 ; Pott et al, 2019 ), and numerous odor characteristics are distinguishable by the developed human sense of olfactory ( Pavagadhi and Swarup, 2020 ). Only a few dozen volatiles contribute substantially to flavor and only when their concentrations exceed the olfactory threshold ( Czerny et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar and acid are considered to be the basic compounds for fruit flavor formation ( Baldwin et al, 2008 ; Bastias et al, 2011 ), while the volatiles form the characteristic flavor compounds of different fruits ( Baldwin et al, 2008 ; Du et al, 2015 ). Therefore, it is not scientifically valid to judge tomato flavor on taste alone; instead, taste and odor should both be assessed to comprehensively evaluate the flavor ( Pavagadhi and Swarup, 2020 ). The results of the DTOPSIS evaluation in the present study indicated that tomato accessions with a preferred (i.e., “better”) flavor either scored high in the taste evaluation or had a strong odor.…”
Section: Discussionmentioning
confidence: 99%
“…These dipeptides contribute to flavors derived enzymatically in Allium species [34]. The presence of these compounds at relatively higher levels in authenticated samples could potentially explain the stronger sensory impression when compared to other cultivars [3,29]. Figure 4B).…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…Some key metabolite features annotated here through molecular networking appeared to be dependent on sampling location ( Figs 1B and 1C). Moreover, the relative abundances of metabolites associated with flavor and aroma could account for the difference in taste and smell between samples [29]. To provide an unbiased (i.e.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation